(Post‐)Tonal Key Relationships in Scriabin's Late Music. (21st August 2017) - YUNEK, JEFFREY SCOTT
ABSTRACT: One of the leading theories of Scriabin's late music is that his collections are chords that are related through invariant transposition. Whereas this theory is effective in relating symmetrical collections such as the octatonic, it cannot relate asymmetrical collections such as Scriabin's mystic chord. In order to overcome this issue, I explore Scriabin's own understanding of his harmonic language and interpret it through his personal statements, philosophical beliefs and theoretical training. I reveal that Scriabin thought of his collections not as chords, but as closely related keys ( tonalnosti ). Although close key relationships are tonal in nature, this relationship can be transferred to post‐tonal music when defined as a maximally invariant transposition. Accordingly, this operation accounts for transpositional relationships between symmetrical and asymmetrical collections in Scriabin's late music, suggesting that his late harmonic language equates to a rapid succession of closely related keys. This theory is applied to excerpts spanning the late period, from Op. 58 to Op. 74, with extended applications to Op. 63 No. 2 and Op. 73 No. 2.